CLUSROOF: Integrating Descriptive Analytics and K-Means Algorithm for Nishin Metal Corporation (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This project created a web-based system called ClusRoof for Nishin Metal Corporation, a company that offers commercial and industrial roofing services. The system helps the company manage customers and projects while also using the K-Means Algorithm to group customers based on their service requests. It includes an easy-to-use dashboard that shows important information such as project cost, duration, and type of service. The system also helps manage job orders, materials used, and service history. It was developed using Python, PHP, MySQL, JavaScript, and CSS, making it functional, secure, and simple to use. The system was tested and evaluated using the ISO 25010 standard, which checks quality in areas like functionality, reliability, usability, efficiency, and security. Based on feedback from both users and technical evaluators, ClusRoof was found to be effective, user-friendly, and reliable. It successfully met its goals by giving accurate customer grouping, clear data displays, and useful insights to help the company make better decisions. For future improvements, it is recommended to add new features like real-time payment options, automatic email notifications for inquiries, and an inventory module for materials. Continuous updates, security checks, and user support are also advised to keep the system running smoothly. Overall, this project shows that ClusRoof can help improve business processes, and customer service.